Coupling an adaptive protection system with an energy management system for microgrids - Núñez Mata, Óscar Fernando (2019)
Energy Management Systems (EMS) are control schemes in charge of defining the optimal scheduling of dispatchable units in a microgrid. Output set points from the EMS could be exploited in other control loops that may benefit from the microgrids expected behavior improving their operation. In this context, this paper proposes a novel coupled operation of an EMS with an Adaptive Protection System (APS), such that the information of the EMS serves to compute the parameters of the protective devices deployed in a microgrid. This aspect is formalized in the present proposal based on already developed APS and EMS frameworks. To evaluate the performance of the proposal, the microgrid installed in Huatacondo, north of Chile, was used as a test-bed. The obtained results indicate that considering the information provided to the APS form the EMS improves the overall performance of the microgrid in case of failure, despite the operating conditions. This also indicates that moving towards an integrated design of the EMS and APS might enhance the behavior (robustness) of a microgrid (as a whole) in case of failures or contingencies.